Prevalence of Speech Handicap among Patients Treated for Head Neck Cancer in a Specialized Hospital - Parvez, Nahid (Jour Med Resh and Health Sci, 2019)
Abstract In Bangladesh many head neck cancer patients are suffering different complications including speech difficulties after completing treatment. This study represents the prevalence of speech handicap among patients treated for head neck cancer in Bangladesh. This study was aiming to find out the prevalence of speech handicap among patients treated for head neck cancer in Bangladesh. A descriptive type of cross sectional study of 70 participants was conducted. The sample was selected by using purposive sampling procedure. Data were collected from 70 participants through face to face interview. Descriptive statistics were used for data analysis. More than half of the participants 60% were male and highest number participants, 36% (25) were in the age range of ?60 years. The highest number of participants 36% was found as diagnosed in the anatomic of site of buccal mucosa and they 14 rated their speech at severe level and 12 at moderate to severe level. Among the tongue cancer diagnosed participants 7 rated their speech as severe level, 9 at moderate to severe level. Among the larynx cancer diagnosed participants 5 were rated their speech at severe level, 12 rated as moderate to severe level and 2 rated as within normal limit. Among the participants those were diagnosed as cancer in the palate 2 rated their speech at severe level and 5 were rated as moderate to severe level. This study helps to establish a collaborative treatment approach for head neck cancer patients and improve the referral system to speech & language therapy services in Bangladesh. Key Words: Prevalence, Speech Handicap and Head Neck Cancer.